2023
DOI: 10.3389/fbioe.2023.1208711
|View full text |Cite
|
Sign up to set email alerts
|

Smooth and accurate predictions of joint contact force time-series in gait using over parameterised deep neural networks

Abstract: Alterations in joint contact forces (JCFs) are thought to be important mechanisms for the onset and progression of many musculoskeletal and orthopaedic pain disorders. Computational approaches to JCFs assessment represent the only non-invasive means of estimating in-vivo forces; but this cannot be undertaken in free-living environments. Here, we used deep neural networks to train models to predict JCFs, using only joint angles as predictors. Our neural network models were generally able to predict JCFs with er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To the authors’ knowledge, this is the first study showing such a comprehensive set of experimental measures and parameters, collected with the aim to fully characterize an individual from a biomechanical and neuromuscular standpoint. With a larger sample size at hand, one could apply data extraction and analytics approaches—eventually supported by machine learning or AI-based methods—to get insights into the mechanisms behind the loss of muscle force ( Giarmatzis et al, 2020 ; Yeung et al, 2020 ; Liew et al, 2023 ; Moghadam et al, 2023 ; Rabbi et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, this is the first study showing such a comprehensive set of experimental measures and parameters, collected with the aim to fully characterize an individual from a biomechanical and neuromuscular standpoint. With a larger sample size at hand, one could apply data extraction and analytics approaches—eventually supported by machine learning or AI-based methods—to get insights into the mechanisms behind the loss of muscle force ( Giarmatzis et al, 2020 ; Yeung et al, 2020 ; Liew et al, 2023 ; Moghadam et al, 2023 ; Rabbi et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future study shall consider a well-designed experimental setup that match the real badminton court under training and match conditions. Second, only the discrete and key datapoints were applied to train and test the intelligent statistical models, without considering the time-varying features; thus, other machine learning algorithms, deep learning algorithms, and convolutional neural networks (such as long short-term memory, LSTM) may be utilized for the monitoring and prediction of loading accumulation ( Shao et al, 2022 ; Liew et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In term of model prediction, a recent study reported that including data on walking and running was no better than including walking or running alone (B. X. Liew et al, 2023 ). Nevertheless, a more diverse dataset in machine learning can benefit the model by improving generalization, reducing bias, and enhancing robustness to variations in individual characteristics.…”
Section: Discussionmentioning
confidence: 99%